Mechanical Properties of Styrene-Butadiene Rubber Composites Made with Mixed Local Libyan Grasses “Halfa and R’tem” - Anour Shebani; Hussein Etmimi; Alsbani, Tarik Yerro; Osama Ahtewish (AlQalam Journal of Medical and Applied Sciences, 2025)
The paper aims to investigate the effect of using a mixture of two local Libyan grasses (Halfa and R’tem) as reinforcing fillers for styrene-butadiene rubber (SBR). SBR composites with different filler content (10, 20, 30, and 40 wt%) were prepared by extrusion process. The effect of these grasses on the mechanical properties such as tensile strength, elongation at break, impact strength, and micro-hardness was investigated. Results indicated that the highest stress at break value was exhibited by the composite made with 20% filler content. Contrarily, all composites containing 10, 30, and 40 wt% of the filler had lower stress at break than that of pure SBR. Results also indicated that the addition of these grasses significantly decreased the elongation at the break of the SBR polymer. As the amount of the filler increased, the elongation at the break of SBR decreased significantly. However, the impact strength of SBR composites showed a considerable increase with the addition of the same grasses, where composites containing 20 wt% filler had the maximum impact strength value. Similarly, the micro-hardness of the composite was increased with the addition of the grasses, where composites containing 40 wt% grasses had the maximum micro-hardness value. Optical microscope images demonstrated various defects in composites made with 10, 30, and 40 wt% grass content, including the formation of filler aggregation and the presence of bubbles. None of these were observed in a composite made with 20 wt% grass content, which was in good agreement with the mechanical properties results.